Investigações em geometria plana com interfaces digitais: um estudo sobre Homotetia - Lima, Nilo Silveira Monteiro de (2016)
This study was aimed to develop a teaching strategy for the use of technologies in activities/problems linked to plane geometry, with the subject "dilation" as main mathematical principle, with the intent of highlighting the understandings formed by interactive assumptions from the scope of humans-with-media. The research was conducted with a group of teachers attending a master's degree in the area of mathematics education and employed a sequence of activities aimed at analyzing the route marked by exploration of geometric constructions in dynamic environment, from the manipulation of employed media, featuring GeoGebra within a didactic strategy scope. Previous studies, from the bibliography review, resulted in the following guiding question: how to characterize a trajectory of study and research, involving Basic School Mathematics teachers, about the theme "dilation" and related mathematical topics, conducted from a proposal that involves both the resolution of activities by humans-with-media, as the development of fluency in relation to the used interfaces? The research used, as theoretical resources, the constructs concerning to intelligence technologies and humans-with-media, which provided the basis, for the analysis, in order to make it evident that the proposed activities provoked reflections about themes of plane geometry by the subjects, and that occurred some reorganizations of mathematical thought from media manipulations, allowing the knowledge of dilation could be discussed autonomously